THE EFFECT OF WRITTEN PEER FEEDBACK ON THE COMPOSITIONS OF THE TENTH GRADERS’ (RETAIN, 2016)
THE EFFECT OF WRITTEN PEER FEEDBACK ON THE COMPOSITIONS OF THE TENTH GRADERS’ Mohammad Farikh Ihwayudi English Education, Language and Art Faculty, State University Surabaya mohammadihwayudi@mhs.unesa.ac.id Abstract This research is concerned with the students’ writing ability after the implementation of a written peer feedback. This research uses an experimental design, the data of which are the scores of the experimental and control groups obtained from pre and post-test. The researcher also calculates the scores of each component in order to know whether or not they are significantly improved. Moreover, the data used only the scores of the post-test which are calculated using Independent Sample T-test of SPSS 16.0. The result shows that the scores of the experimental group are higher than those of the control one which means that the experimental group can reduce the errors and mistakes of writing components. It can be concluded that written peer feedback is effective for improving students’ writing ability. Key Words: Writing, Written Peer Feedback Abstrak Penelitian ini berkaitan dengan kemampuan menulis siswa setelah pelaksanaan umpan balik rekan secara tertulis. Penelitian ini menggunakan desain eksperimen, data dari penelitian ini adalah nilai siswa dari kelompok eksperimen dan kontrol yang diperoleh dari pre dan post-test. Peneliti juga menghitung nilai dari masing-masing komponen menulis dalam rangka untuk mengetahui apakah mereka meningkat secara signifikan atau tidak. Sedangkan, data yang digunakan hanya nilai dari post-test yang dihitung dengan menggunakan Independent Sample T-test SPSS 16.0. Hasil penelitian menunjukkan bahwa nilai dari kelompok eksperimen lebih tinggi dibandingkan kelompok kontrol yang berarti bahwa kelompok eksperimen dapat mengurangi kesalahan penulisan pada komponen menulis. Dapat disimpulkan bahwa ditulis umpan balik rekan efektif untuk meningkatkan kemampuan menulis siswa . Kata Kunci: menulis, umpan balik siswa secara tertulis